2015
DOI: 10.1007/s11936-015-0396-8
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Cardiac Toxicity Due to Cancer Treatment: Role of Cardiac MRI

Abstract: Common cancer treatments including anthracycline-based chemotherapy, tyrosine kinase inhibitors, and thoracic radiation therapy can result in short- and long-term cardiovascular complications with a significant impact on morbidity and mortality. Anthracycline-based chemotherapy and tyrosine kinase inhibitors are associated with left ventricular systolic dysfunction and heart failure. Radiation therapy is associated with restrictive cardiomyopathy, coronary artery disease, as well as pericardial and valvular di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 38 publications
(26 reference statements)
1
15
0
2
Order By: Relevance
“…A decline in left ventricular ejection fraction may be a late manifestation of cardiotoxicity (12) and there has been an increasing focus on early detection of CRC using techniques, such as strain monitoring using Echo (13) and T2-weighted imaging for myocardial edema using CMR (14). There have been algorithms proposed to incorporate these techniques into the CRC screening protocols (15).…”
Section: Discussionmentioning
confidence: 99%
“…A decline in left ventricular ejection fraction may be a late manifestation of cardiotoxicity (12) and there has been an increasing focus on early detection of CRC using techniques, such as strain monitoring using Echo (13) and T2-weighted imaging for myocardial edema using CMR (14). There have been algorithms proposed to incorporate these techniques into the CRC screening protocols (15).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the most important contributing factor for thrombus formation is reduced LVEF and restrictive LV filling pattern. In the context of decreased LVEF, it has been shown that anthracycline treatment can cause decreased the left ventricular mass index (LVMI) which is a surrogate marker for myocyte loss that leads to a decline in LV function . With respect to restrictive filling pattern, pathological studies have shown increased fibrosis in almost all the patients who have been treated with anthracycline .…”
Section: Discussionmentioning
confidence: 99%
“…In the context of decreased LVEF, it has been shown that anthracycline treatment can cause decreased the left ventricular mass index (LVMI) 41 which is a surrogate marker for myocyte loss that leads to a decline in LV function. 42 With respect to restrictive filling pattern, pathological studies have shown increased fibrosis in almost all the patients who have been treated with anthracycline. 43 More recently, CMR studies have reported an increased extracellular volume fraction indicating increased fibrosis from pre-to postanthracycline treatment.…”
Section: Theoretic Reasons For LV Thrombus In Cancer Patientsmentioning
confidence: 99%
“…Other options may be 3D-echocardiography (Toro-Salazar et al, 2016), stress-echocardiography (Jarfelt et al, 2007), and nuclear (Gorla et al, 2016) or magnetic resonance imaging (Meyersohn et al, 2015), but these options are more time-consuming and will probably not provide additional information beyond what can be detected by speckle tracking echocardiography .…”
Section: Cardiac Surveillancementioning
confidence: 99%